Experience and Discussion: Safeguards for People With Disabilities During the COVID-19 Pandemic in China - Qi, Fei; Wu, Yuqi; Wang, Qi (Frontiers in Public Health, 2021)
The special vulnerability of people with disability (PWD) in the COIVD-19 pandemic has been confirmed by many studies, but data shows that the infection rate of PWD in China is lower than for non-disabled people. This difference can be attributed to the Chinese government’s targeted safeguards for the disabled community during the pandemic, including support for disability empowerment, the establishment of a remote interactive decision-making system, fair vaccine distribution and economic protection for PWD. The professionalism of decision-makers and interaction within the decision-making process were also very important. However, we believe that different national conditions and the institutional advantages of various countries mean that China's experience can be referred to but not copied. Countries should pay more attention to discovering the special needs and obstacles of PWD in the COIVD-19 pandemic: in referring to China's experience, they should explore the protection framework for persons with disabilities and adjust it to their own needs on the basis of national conditions.